Type 1 and Type 2 Epstein-Barr viruses induce proliferation, and inhibit differentiation, in infected telomerase-immortalized normal oral keratinocytes. - Deo R Singh; Scott E Nelson; Abigail S Pawelski; Juan A Cantres-Velez; Alisha S Kansra; Nicholas P Pauly; Jillian A Bristol; Mitchell Hayes; Makoto Ohashi; Alejandro Casco; Denis Lee; Stuart A Fogarty; et al. (PLoS Pathogens, 2022)
Differentiated epithelial cells are an important source of infectious EBV virions in human saliva, and latent Epstein-Barr virus (EBV) infection is strongly associated with the epithelial cell tumor, nasopharyngeal carcinoma (NPC). However, it has been difficult to model how EBV contributes to NPC, since EBV has not been shown to enhance proliferation of epithelial cells in monolayer culture in vitro and is not stably maintained in epithelial cells without antibiotic selection. In addition, although there are two major types of EBV (type 1 (T1) and type 2 (T2)), it is currently unknown whether T1 and T2 EBV behave differently in epithelial cells. Here we inserted a G418 resistance gene into the T2 EBV strain, AG876, allowing us to compare the phenotypes of T1 Akata virus versus T2 AG876 virus in a telomerase-immortalized normal oral keratinocyte cell line (NOKs) using a variety of different methods, including RNA-seq analysis, proliferation assays, immunoblot analyses, and air-liquid interface culture. We show that both T1 Akata virus infection and T2 AG876 virus infection of NOKs induce cellular proliferation, and inhibit spontaneous differentiation, in comparison to the uninfected cells when cells are grown without supplemental growth factors in monolayer culture. T1 EBV and T2 EBV also have a similar ability to induce epithelial-to-mesenchymal (EMT) transition and activate canonical and non-canonical NF-κB signaling in infected NOKs. In contrast to our recent results in EBV-infected lymphoblastoid cells (in which T2 EBV infection is much more lytic than T1 EBV infection), we find that NOKs infected with T1 and T2 EBV respond similarly to lytic inducing agents such as TPA treatment or differentiation. These results suggest that T1 and T2 EBV have similar phenotypes in infected epithelial cells, with both EBV types enhancing cellular proliferation and inhibiting differentiation when growth factors are limiting.